Fatal pulmonary bile embolism associated with acute pancreatitis – a case report and review of the literature - Knapik, Michał; Okoń, Krzysztof; Ulatowska-Białas, Magdalena (Polish Journal of Pathology, 2024)
A 27-year-old woman with jaundice and abdominal pain was admitted to an emergency ward. The diagnostic process showed that gallstones were causing her symptoms. The patient was treated via endoscopic retrograde cholangiopancreatography (ERCP), and during the procedure she suffered a cardiac arrest. Autopsy findings included multiple pulmonary bile emboli as well as features of disseminated intravascular coagulation. Among 22 thus far described cases of bile pulmonary embolism, 13 were associated with medical procedures involving the liver and biliary tract. We present the case report of a pulmonary bile embolism associated with acute pancreatitis treated via ERCP in a woman with gallbladder bile stones.